2017
DOI: 10.20517/2574-1225.2017.12
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic skills training of surgical residents: a comparison of two proficiency-based independent approaches

Abstract: How to cite this article: Bellows CF, Smith AA. Laparoscopic skills training of surgical residents: a comparison of two proficiency-based independent approaches. Mini-invasive Surg 2017;1:126-32. Quick Response Code: Original ArticleThis is an open access article licensed under the terms of Creative Commons Attribution 4.0 International License (https://creativecommons.org/licenses/by/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, as long as the original author is credited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Accordingly, it has been emphasized that curricular requirements, goal setting, testing, and protected training time, i.e., training time incorporated into working-time, protected from clinical responsibilities [21], are essential factors for assuring trainees' commitment to training [22][23][24]. Studies of training programs with proficiency goals and pass/fail criteria found that access to independent home-based training resulted in comparable performance improvements and increased training distribution compared to control groups with access to independent training in simulation centers [25][26][27]. Unlike previous studies, the present study does not investigate independent training, but compares centralized instructor-led training to structured and supported home-based training in laparoscopy.…”
mentioning
confidence: 99%
“…Accordingly, it has been emphasized that curricular requirements, goal setting, testing, and protected training time, i.e., training time incorporated into working-time, protected from clinical responsibilities [21], are essential factors for assuring trainees' commitment to training [22][23][24]. Studies of training programs with proficiency goals and pass/fail criteria found that access to independent home-based training resulted in comparable performance improvements and increased training distribution compared to control groups with access to independent training in simulation centers [25][26][27]. Unlike previous studies, the present study does not investigate independent training, but compares centralized instructor-led training to structured and supported home-based training in laparoscopy.…”
mentioning
confidence: 99%
“…[ 3 4 ] Acquisition of such complex skills requires many hours of hands-on training, which becomes even more challenging in the face of reduced trainee working hours. [ 5 ] Work hour restrictions, pressure to increase theater throughput, and the ethical debate regarding inexperienced surgeons operating on patients meant that the traditional model of surgical training needed to be revised. [ 6 ] As a result, focus has shifted to the use of models and simulators, with the objective of better preparation of trainees for real-life operating room experience.…”
Section: Introductionmentioning
confidence: 99%